Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Use the appropriate substitutions to write down the first four nonzero terms of the Maclaurin series for the binomial (1+3x)^(-1/3)

Sagot :

Answer:

First term=1

Second term=-x

Third term=[tex]2x^2[/tex]

Fourth term =[tex]-\frac{28}{3!}x^3[/tex]

Step-by-step explanation:

We are given that function

[tex]f(x)=(1+3x)^{-1/3}[/tex]

We have to find the  first four non zero terms of the Maclaurin series for the binomial.

Maclaurin series of function f(x) is given by

[tex]f(x)=f(0)+f'(0)x+\frac{1}{2!}f''(0)x^2+\frac{1}{3!}f'''(0)x^3+....[/tex]

[tex]f(0)=(1+3x)^{\frac{-1}{3}}=1[/tex]

[tex]f'(x)=-\frac{1}{3}(1+3x)^{-\frac{4}{3}}(3)=-(1+3x)^{-\frac{4}{3}}[/tex]

[tex]f'(0)=-1[/tex]

[tex]f''(x)=\frac{4}{3}\times 3 (1+3x)^{-\frac{7}{3}}[/tex]

[tex]f''(0)=4[/tex]

[tex]f'''(x)=-4\times \frac{7}{3}\times 3(1+3x)^{-\frac{10}{3}}[/tex]

[tex]f'''(0)=-28[/tex]

Substitute the values we get

[tex](1+3x)^{-\frac{1}{3}}=1-x+\frac{4}{2!}x^2+\frac{-28}{3!}x^3+...[/tex]

[tex](1+3x)^{-\frac{1}{3}}=1-x+2x^2+\frac{-28}{3!}x^3+...[/tex]

First term=1

Second term=-x

Third term=[tex]2x^2[/tex]

Fourth term =[tex]-\frac{28}{3!}x^3[/tex]